KEBERADAAN DAN FUNGSI MITOS BAGI KELESTARIAN SITUS TINGGALAN MEGALITIK DI DESA DODA, KECAMATAN LORE TENGAH, KABUPATEN POSO - I Wayan Nitayadnya (Multilingual, 2013)
Myth  is one of the pillars in preserve the cultural herritage. It is taught the norms, values, and the value of ancestor’s religy. These formed the characters of Doda’s socety particularly, and  Lembah Besoa’s society generally.  The myth which have been existed in the Doda’s village is revealed in this paper. The other revelation is how to understand the existence and function of the myth, in that site. The Method of research which is applied in this paper are literature and  analythic-descriptive methode. The study is written in the narrative text. In the result, it is shown that the myths which were spread are Pamulana Ngamba Behoa, Pamulana Wanua Doda, Tolelembunga. Topehebe, and  Tadulako.  Those myths have existed recently,  and the cultural herritages which has been told in the myth have been sacredly preserved by the local people. Those myths have function to create the awareness of the society toward the collective history, the awareness of social solidarity, the awareness of ancestor heroism and to strengthened the faith of the magical nature. These aspects make the society of Doda and Besoa have positive implication toward the preservation of megalithic culture site. They are together guarding, caring, and preserving the  cultural herritage of their ancestor. This attitude is formed by the existence of the myth which is acknowledged as the true.